Assessing the feasibility and prerequisites for establishing a sovereign wealth fund in South Africa - Mbalo, Usiphile (Graduate School of Business (GSB), 2025)
In 2023, the Sovereign Wealth Fund (SWF) Institute reported that assets under management for the 173 global SWFs totalled in excess of US$ 11.5 trillion, with Africa contributing only US$ 132.69 billion. These funds are invested both domestically and internationally, resulting in a favourable impact on their own countries. The objective of the present study was to determine what the prerequisites to create a SWF in South Africa. The research delineates a SWF and analyses the history thereof. The study additionally examines investment methods, governance structures, and frameworks for SWF. Within the South African context, a well-managed SWF may enhance intergenerational equity, foster inclusive growth, and bolster fiscal resilience amid global volatility and domestic socioeconomic problems. Revenue from mineral resources or the divestiture of state-owned assets may enable a SWF to stabilise South Africa's economy against foreign shocks, diminish reliance on debt, and furnish a sustainable source of revenue for social and infrastructure development. The 2020 announcement by the former Minister of Finance set an intention for the South African Government to establish a SWF by allocating ZAR 30 billion, as well as exploring various funding solutions through the sale of spectrum, allocation of petroleum, gas, and mineral rights, sale of non-core state assets, and future budget surpluses. The announcement was received with enthusiasm; however, a persistent question lingered: can South Africa establish a SWF, or is it simply an elusive ambition? The present study gathered data through semi-structured interviews with diverse industry executives in finance, development finance, and asset management. The researcher employed a qualitative exploratory research methodology to obtain insights regarding South Africa's potential for establishing a SWF. The study's major findings indicated that a SWF should be seen as a savings vehicle capable of aiding future generations considering the country's escalating debt. The SWF may potentially support South Africa during economic difficulties. For South Africa to establish a SWF, it must be founded on a robust legislative framework that enables the fund to be agile, competitive, sustainable, governed effectively, and insulated from political interference. South Africa possesses a pre-existing model from which it can derive insights and enhance to establish the fund.